Analisis Perbandingan Dempster Shafer dan Case Base Reasoning Dalam Diagnosis Penyakit Mastocytosis Menggunakan Metode Perbandingan Eksponensial - Ervin Lamhot Tua Sitinjak (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Diseases pose a major challenge in the medical world. Accurate and precise diagnosis is a crucial key in disease management, including the case of mastocytosis. Mastocytosis is a disorder characterized by the proliferation of mast cells that can affect various organ systems in the human body. There are various variations of mastocytosis, but they can generally be categorized into two main types: cutaneous mastocytosis, which primarily affects the skin and is the most common form, and systemic mastocytosis, which is a more severe form involving the accumulation of mast cells in organs and tissues throughout the body, not just the skin. Planning a successful course of therapy and providing a positive outlook for patients heavily relies on an accurate and timely diagnosis of mastocytosis. This study utilizes an exponential comparison strategy to compare and contrast the Dempster-Shafer (DS) and Case Based Reasoning (CBR) techniques in detecting mastocytosis. The Dempster-Shafer technique is employed in this study to gather and evaluate data from various ambiguous and inadequate sources. This method utilizes the theory of mass variability to represent uncertainty in disease diagnosis. On the other hand, Case Based Reasoning is an approach that relies on past experiences and utilizes existing knowledge in the form of previously encountered cases to make diagnoses. In this study, exponential comparison is used to assign greater weight to certain attributes considered more important in the diagnosis process. This exponential comparison method allows for more flexible attribute weighting, enabling more accurate modeling of symptoms and related factors in mastocytosis. The aim of this research is to use the exponential comparison approach to develop, analyze, and compare both strategies in detecting mastocytosis. With the lowest rate for cutaneous mastocytosis and the highest percentage for systemic mastocytosis, the research findings indicate that both approaches yield comparable results. The Dempster-Shafer approach has proven to be more accurate in mastocytosis diagnosis when comparing the calculations of these two methods with the exponential comparison method